The influence of mind mapping on computational thinking skills and self-efficacy in students’ learning of graphical programming - Guo, Rong; Zheng, Yan; Miao, Haifei (Frontiers in Education, 2024)
Computational thinking is regarded as an essential skill for students in the 21st century, and programming is one of the means to cultivate it. This study introduces mind mapping into graphical programming to visualize the cognitive process of computational thinking, aiming to enhance students’ computational thinking skills. After a semester of teaching experiments, independent-sample t-tests and paired-sample t-tests were conducted on the data, revealing significant improvements in both computational thinking skills and self-efficacy among the students in the experimental group. Further analysis of the data showed significant enhancements in their algorithmic thinking and modeling, as well as pattern recognition and evaluation sub-skills, while abstraction and decomposition sub-skills did not show significant improvement. Additionally, the experimental group demonstrated significant improvements to varying degrees in five dimensions of computational thinking self-efficacy: creativity, algorithmic thinking, collaboration skills, critical thinking, and problem-solving abilities.